Fiodor Dostojewski - Biesy / proj. graf. Tomasz Dobrowolski, fot. Zbigniew Treppa. - Dobrowolski, Tomasz (fotografia) (Teatr Wybrzeże, 1992)
Plakat przedstawienia z 1992 r. Na plakacie sześcian z twarzą mężczyzny.